2019
DOI: 10.1007/s11242-019-01357-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved Eddy-Viscosity Modelling of Turbulent Flow around Porous–Fluid Interface Regions

Abstract: The RANS modelling of turbulence across fluid-porous interface regions within ribbed channels has been investigated by applying double (both volume and Reynolds) averaging to the Navier-Stokes equations. In this study turbulence is represented by using the Launder and Sharma (1974) low-Reynolds number k − ε turbulence model, modified via proposals by either Nakayama and Kuwahara (2008) or Pedras and de Lemos (2000), for extra source terms in turbulent transport equations to account for the porous structure. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…The key reason that the current LES calculations include these three Re numbers is that the onset and evolution of K-H instabilities can be clearly captured and discussed in this range of Re numbers since it presents a wide range of different flow structures. Moreover, not only the current study, but also the previous studies about the flow physics over and inside the porous block used this range of Re numbers in their work [19,20,24,[60][61][62]. At Re=3600, the formation of K-H instabilities is retarded downstream, starting approximately at "Point A" with 𝑋/𝐷~4.6, as marked in Figure 12(a).…”
Section: Kelvin-helmholtz Instabilitymentioning
confidence: 78%
“…The key reason that the current LES calculations include these three Re numbers is that the onset and evolution of K-H instabilities can be clearly captured and discussed in this range of Re numbers since it presents a wide range of different flow structures. Moreover, not only the current study, but also the previous studies about the flow physics over and inside the porous block used this range of Re numbers in their work [19,20,24,[60][61][62]. At Re=3600, the formation of K-H instabilities is retarded downstream, starting approximately at "Point A" with 𝑋/𝐷~4.6, as marked in Figure 12(a).…”
Section: Kelvin-helmholtz Instabilitymentioning
confidence: 78%
“…It was also found that as the permeability increased much of the fluid passes through the baffles the recirculation bubbles become weaker and are shifted downstream. As also confirmed by a recent numerical study from the authors' group, Al-Aabidy et al [17], the development of reliable RANS models for turbulent flow through passages with porous regions, depends on the availability of reliable local flow data. This means that to extend the effective use of RANS models to the prediction of cooling flows through rotating passages with porous regions, there is a need for local flow experimental data.…”
Section: Introductionmentioning
confidence: 80%
“…The sediment layer was divided into two zones by porosity, namely, a porous medium region with uniform porosity ϕ0$$ {\phi}_0 $$ and a transition region. According to Al‐Aabidy et al (2020), the transition layer's thickness was set to 2 D p , and the porosity of the transition region ϕ$$ {\phi}^{\prime } $$ was computed using Equation (). The turbulence level near the SWI will be overstated if the thin transition layer between the overlying water and homogenous porous medium area is not taken into account (Kuwata & Suga, 2013).…”
Section: Methodsmentioning
confidence: 99%